Who Should They Relate To? A Study For the Identification and Analysis of Criteria to the Partners’ Selection in Inter-Organizational Networks - Denise Rossato Quatrin; Breno Augusto Diniz Pereira (BBR: Brazilian Business Review)
The selection of partners is strategic in inter-organizational networks. One of the most important aspects is the definition of criteria for selection, that are the minimal characteristics required from those prospected. This study aimed to identify the most important criteria for the selection of members in horizontal inter-organizational networks, also describing their influence on network activities. First, we applied 120 questionnaires to managers of inter-organizational networks to identify the degree of importance of criteria previously treated in the literature. After, we interviewed 16 managers enabling us to identify other criteria, as well as understanding their influence on network activities. All of the 20 criteria from the literature were considered with significant importance by managers and the following criteria were added: trustworthiness, entrepreneur’s profile and company lifetime. The results aim to contribute to the selection of partners and provide information for the construction of the inter-organizational networks literature.